2001
DOI: 10.1680/macr.2001.53.5.311
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of wastewater generated at concrete plants in Florida in the production of fresh concrete

Abstract: Wastewater produced at ready-mixed concrete plants from the cleaning of the concrete truck's drum has recently been banned from direct disposal to ground or surface waters. Recent environmental regulations require readymixed concrete plants to manage and contain wastewater by the use of a reclamation system until it is environmentally acceptable for discharge. The objective of this study was to investigate water quality standards in Florida and the possibility of reusing concrete wastewater as aggregate irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 2 publications
0
19
0
1
Order By: Relevance
“…Sludge water that meets the requirements of ASTM specification C94 (ASTM C94, 2004) may be reused as mixing water for concrete production with no significant effects on the properties of the concrete (Borger et al, 1994;Chini and Muszynski, 2001;Su et al, 2002). It has been found that fine-filler effects and a reduction of the actual water/cement ratio due to the fine solids content of sludge water lead to a reduction in concrete capillary water absorption and porosity, and possibly improve the durability of the concrete (Sandrolini and Franzoni, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sludge water that meets the requirements of ASTM specification C94 (ASTM C94, 2004) may be reused as mixing water for concrete production with no significant effects on the properties of the concrete (Borger et al, 1994;Chini and Muszynski, 2001;Su et al, 2002). It has been found that fine-filler effects and a reduction of the actual water/cement ratio due to the fine solids content of sludge water lead to a reduction in concrete capillary water absorption and porosity, and possibly improve the durability of the concrete (Sandrolini and Franzoni, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Concrete mixed with sludge water containing residual cement tends to exhibit a shorter setting time and lower flowability (Su et al, 2002). Nevertheless, the complete recycling of sludge water has been considered in concrete mixing plants because of the great benefit in terms of disposal cost reduction and environmental conservation (Chini and Muszynski, 2001;Su et al, 2002;Paolini and Khurana, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of being disposed of, sludge water that meets the requirement of ASTM C94 specification [2] can be recycled and used as mixing water for concrete production if there are no significant effects on mechanical properties of concrete [1,3,4]. According to Sandrolini and Franzoni, fine-filler effects and actual water/cement ratio reduction due to fine solids contents in sludge water leads to the reduction of concrete capillary water absorption and porosity, and possibly improve the durability of concrete [5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, aggregate base materials mixed with RCM I and dolomite performed better with respect to Mp and rutting than sand and crashed gravel blend (Barksdale et al, 1992). Chini et al (2001) .showed that compressive strength of the RCM mixtures with natural aggregates decreased as percentage of RCM in the mixture increased. Hanks and Magni (1989) showed RAP-aggregate mixture had adequate bearing capacity, good drainage, and good durability but the bearing capacity of RAPaggregate mixtures decreased with an increase in RAP content.…”
mentioning
confidence: 99%